Is stereotactic body radiotherapy an effective treatment in metastatic lung cancer with oligoprogressive disease?. (4th March 2023) - Aquilano, Michele; Loi, Mauro; Visani, Luca; Livi, Lorenzo; Nuyttens, Joost J.
Abstract: Background: Oligoprogression (OPD) is defined as a condition where limited progression (1–3 metastases) is observed in patients undergoing systemic cancer treatment. In this study we investigated the impact of stereotactic body radiotherapy (SBRT) in patients with OPD from metastatic lung cancer. Material and Methods: Data from a cohort of consecutive patients with SBRT treated between June 2015 and August 2021 were collected. All extracranial metastatic sites of OPD from lung cancer were included. Dose regimens consisted of mainly 24 in 2 fractions, 30–51 Gy in 3 fractions, 30–55 Gy in 5 fractions, 52.5 Gy in 7 fractions and 44–56 Gy in 8 fractions. Kaplan–Meier method was used to calculate Overall Survival (OS), Local Control (LC), and Disease-Free Survival (DFS) from the start date of SBRT to the event. Results: Sixty-three patients, 34 female and 29 males were included. Median age was 75 years (range 25–83). All patients received concurrent systemic treatment before the start of the SBRT: 19 chemotherapy (CT), 26 CT plus immunotherapy (IT) or Tyrosin kinase inhibitors (TKI) and 18 IT/TKI. SBRT was delivered to the lung ( n  = 29), mediastinal node ( n  = 9), bone ( n  = 7), adrenal gland ( n  = 19), other visceral metastases (1) and other node metastases ( n  = 4). After a median follow-up of 17 months, median OS was 23 months. LC was 93% at 1 year and 87% at 2 years. DFS was 7 months. According to our results, there was no statistically significant correlation between prognostic factors and OS after SBRT in OPD patients. Conclusions: Median DFS was 7 months, translating into the continuation of effective systemic treatment as other metastases grow slowly. In patients with oligoprogression disease, SBRT is a valid and efficient treatment that may enable postponing the switch of systemic line.